PENGGUNAAN MEDIA MARAKAS PINGUIN DALAM MENINGKATKAN KETERAMPILAN POLA RITMIS ANAK USIA DINI - Itot Bian Raharjo; Sholichatun Inaroh (LP2MP3M, INSTITUT SENI INDONESIA SURAKARTA, 2019)
ABSTRACT Based on the observations of researchers, the ability of children’s rhythmic patterns has not developed opti-mally because the media used by teachers in learning in the form of glass bottles filled with water and the absence of writing tone patterns, so that children are less interested in playing and easy to forget the rhythmic patterns played. So researchers use maracas penguins media to improve the ability of rhythmic patterns. This research approach is PTK with three cycles. Subjects were children aged 5-6 years of PAUD SAKA SEKOLAH ALAM KADIRI Jajar Village, Wates District, Kediri Regency. Data collection instruments in the form of teacher observation sheets, children’s assessment sheets and documentation in the form of photo activities. Assess-ment techniques in the form of performance. This study uses quantitative descriptive data analysis. The results showed that after the first cycle action the ability of the child in 30% accuracy, 70% in the second cycle and 90% in the third cycle, while the aspect of the rhythm pattern in the first cycle was 40%, 70% in the second cycle, and 90% in the third cycle. Thus the conclusion of this study is through maracas media penguins can improve the ability of rhythmic patterns in children aged 5-6 years of PAUD SAKA SEKOLAH ALAM KADIRI Kediri Regency, so this research hypothesis is accepted